2021
DOI: 10.3390/jcm10143182
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Conus Medullaris in 629 Healthy Japanese Individuals

Abstract: The conus medullaris typically terminates at the L1 level; however, variations in its level and the factors associated with the conus medullaris level are unclear. We investigated the level of conus medullaris on magnetic resonance imaging in healthy volunteers. In total, 629 healthy adult volunteers (≥50 individuals of each sex and in each decade of age from 20 to 70) were enrolled. The level of the conus medullaris was assessed based on the T2-weighted sagittal magnetic resonance images, and factors affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…They concluded that most individuals (92.2%) have conus termination at the T12-L1 level, whereas 7.8% have the conus cranial at the T12 level. The authors found that the caudal levels of the conus were significantly associated with lower height and a smaller pelvic index, thus further determining a gendered difference associated with the terminal level of conus medullaris [12]. The work of Gatonga, Ogeng'o, and Awori on 112 cadavers revealed the lower limit of conus medullaris at or below the upper one-third of the L2 level [13].…”
Section: Discussionmentioning
confidence: 97%
“…They concluded that most individuals (92.2%) have conus termination at the T12-L1 level, whereas 7.8% have the conus cranial at the T12 level. The authors found that the caudal levels of the conus were significantly associated with lower height and a smaller pelvic index, thus further determining a gendered difference associated with the terminal level of conus medullaris [12]. The work of Gatonga, Ogeng'o, and Awori on 112 cadavers revealed the lower limit of conus medullaris at or below the upper one-third of the L2 level [13].…”
Section: Discussionmentioning
confidence: 97%
“…The conus medullaris, the terminus of the spinal cord, contains the S3–5 myelomeres that include the sacral motor neurons, and injury of the conus from lesions such as spinal cord tumors or vascular malformations supplied by the artery of Desrpoges-Gotteron are associated with features of cauda equina syndrome including saddle anesthesia, loss of bowel and bladder reflexes, and incontinence of sphincter dysfunction 20–22 . Although there is some anatomic variability among individuals, the terminus of the spinal cord is typically at the L1 vertebral level 8,23 . The distal portion of the spinal cord just proximal to this is termed the epiconus and contains the myelomeres for the L4–S1 roots 7,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical presentations of myelopathy from cervical stenosis and neurogenic claudication from lumbar stenosis are well-characterized and familiar to most clinicians, the neurological signs and symptoms of thoracolumbar junction area stenosis may not conform to either clinical pattern 1,4–7 . The spinal cord terminus in adults is usually near the L1 vertebral body, and stenosis in the T10–L1 area results in compression of the distal spinal cord just above the conus medullaris, a site that may not produce hyper-reflexia and the Babinski sign typical of spinal cord compression at higher spinal levels nor the typical lower motor neuron pattern of cauda equina compression 8 . This portion of the spinal cord has been termed the epiconus, and compression at this location has been the subject of only a small number of case series that have reported mixed picture of upper and lower motor neuron findings 9 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory or motor symptoms such as clumsiness, numbness, weakness, and gait disturbance; severe low back pain; spinal trauma or congenital spinal deformity history; brain or spinal surgery history; and neurological diseases like neuropathy and cerebral ischemic disease and neuropathy along with females with pregnancy, worker's compensation received by individuals or presenting with symptoms post motor vehicle accident, and those in whom there was difficulty in examining the sagittal radiograph parameters of lumbosacral transitional anomalies or spinal malformations were excluded from the study. Visual analog scale measurements of the lower back, buttock, and leg pain were taken before deciding on the inclusion of patients in this study and excluded cases with severe pain anywhere above 80 mm as cases with severe pain 8) . Finally, a total of 627 relatively healthy subjects (307 males and 320 females; mean age, 49.6±16.5 years) with appropriate imaging results were enrolled; at least 50 subjects from each sex were included in the following age groups: 20-29, 30-39, 40-49, 50-59, 60-69, and 70-79 years (Table 1).…”
Section: Study Populationmentioning
confidence: 99%